Analysis of Factors Affecting Foreign Direct Investment (FDI) in Indonesia - Desi Fitriyani; Thomas Andrian (International Journal of Economics, Management and Accounting (IJEMA), 2024)
This study aims to analyze the factors affecting foreign direct investment in Indonesia. The data used is dynamic panel data for the period 2010 to 2022, the dependent variable used is foreign direct investment in Indonesia, and the independent variables used are infrastructure reflected by the total length of provincial roads, macroeconomic stability reflected by the consumer price index, and market size reflected by gross regional domestic product per capita. The analytical tool used is multiple linear regression with the generalized method of moment (GMM) analysis method. The results showed that infrastructure, macroeconomic stability, market size, and FDI in the previous year had a significant effect on FDI in Indonesia.